Polarization-multiplexed metaholograms with erasable functionality. (13th March 2023) - Zhou, Shaolin; Liu, Liang; Chen, Zhijian; Ansari, Muhammad Afnan; Chen, Xianzhong; Chan, Mansun
Abstract: The unprecedented capability of metasurfaces in pixel-wise-level accurate light manipulation has enabled the realization of polarization-multiplexed metasurface holograms in a single or multiple channel. However, most metasurfaces are static and unable to realize active or tunable wave control in many scenarios. We introduce an erasable functionality for multi-channel metasurface holograms based on active phase tuning, which is realized using the nonvolatile chalcogenide phase change alloy of GeSbSeTe (GSST). Upon the incidence of linearly or circularly polarized waves, polarization-dependent holograms constructed using amorphous GSST (a-GSST) elliptical pillars are achieved because of the complete phase control. The a-GSST holograms feature a subwavelength spatial resolution for all elliptical pillars, with local transmittances ranging from 66% to 90%. Benefiting from the amorphous-to-crystalline phase transition of GSST, the hologram functionality can be completely erased because the crystallized pillars cannot provide the effective propagation modes required by the anisotropic phase modulations in the operating wavelength range. The unique properties of the proposed polarization-multiplexed holograms with erasable functionality offer more degrees of freedom and have potential applications in many fields, such as anti-counterfeiting, encryption, and holographic sources.